1995
DOI: 10.1038/373341a0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo neurotrophic effects of GDNF on neonatal and adult facial motor neurons

Abstract: Motor neurons require neurotrophic factor(s) for their survival during development and for maintenance of function in adulthood. In vivo studies have shown that motor neurons respond to a variety of molecules, including ciliary neurotrophic factor, members of the neurotrophin family, and the insulin growth factor IGF-1 (refs 3-13). Here we investigate the potential motor neuron neurotrophic effects of glial-cell-line-derived neurotrophic factor (GDNF), initially identified as a neurotrophic factor for substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
328
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(342 citation statements)
references
References 21 publications
12
328
0
2
Order By: Relevance
“…Nerve injuries induce a variety of molecular responses such as neurotrophic factors, cytokines, growth factors, and extracellular molecules that may be involved to some extent in the regeneration of injured neurons (Skene, 1989;Doster et al, 1991;Sendtner et al, 1992;Schnell et al, 1994;Yan et al, 1995;Fournier and McKerracher, 1997). In the course of searching the molecules whose expression is altered in adult rat motor neurons of facial nucleus after axotomy, we found that Shh expression was upregulated from 24 hr after axotomy and declined at 4 weeks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nerve injuries induce a variety of molecular responses such as neurotrophic factors, cytokines, growth factors, and extracellular molecules that may be involved to some extent in the regeneration of injured neurons (Skene, 1989;Doster et al, 1991;Sendtner et al, 1992;Schnell et al, 1994;Yan et al, 1995;Fournier and McKerracher, 1997). In the course of searching the molecules whose expression is altered in adult rat motor neurons of facial nucleus after axotomy, we found that Shh expression was upregulated from 24 hr after axotomy and declined at 4 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that facial nerve axotomy in neonatal rats induces motor neuron death of the facial nucleus, whereas most of the neurons survive in adult rats (Graeber et al, 1998). The lack of regenerative properties of neonatal rat neurons is partly attributable to insufficient trophic supports from their target (Skene, 1989;Sendtner et al, 1992;Schnell et al, 1994;Yan et al, 1995;Fournier and McKerracher, 1997), but the molecular mechanisms of the axotomy-induced neuronal death in neonatal rats remain to be fully elucidated. To investigate the mechanisms that are responsible for promotion of motor neuron survival, we searched molecules whose mRNA expression is altered after nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis to explain these results is that the survival of forebrain neurons in mammalian brain is determined by multiple signaling pathways [such that the removal of one signaling pathway is compensated for by others (Snider, 1994;Meyer-Franke et al, 1995)]. The anatomical basis of redundant trophic signaling may lie in the fact that neuronal populations in the mammalian forebrain generally make and receive a large number of (often reciprocal) synaptic connections with several neuronal populations (Snider, 1994); glial and auto/ paracrine mechanisms of neurotrophin release may also contribute to redundant neurotrophic signaling (Acheson et al, 1995;Yan et al, 1995). By comparison, because the song-control system in the avian forebrain contains large populations of neurons that typically contact a limited number of afferent inputs and efferent targets in a serial, nonreciprocal manner (Bottjer et al, 1989;Johnson et al, 1995;Vates and Nottebohm, 1995), the loss of even one input or target removes a major source of trophic support and can result in extensive anterograde or retrograde neurodegeneration Bottjer, 1993, 1994;Akutagawa and Konishi, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of BNIP3 mRNA in facial motoneurons after nerve axotomy Transection of the facial nerve in the neonatal rat triggers the apoptosis of MNs (Oppenheim et al, 1995;Sendtner et al, 1992;Sun and Oppenheim, 2003;Yan et al, 1995). To test whether BNIPs are involved in apoptosis in vivo, we examined the induction of BNIP mRNAs following facial nerve axotomy (Fig.…”
Section: A B C D E Fmentioning
confidence: 99%